2019
DOI: 10.1080/16066359.2018.1530765
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal monitors to assess alcohol consumption in real-time and real-life – a qualitative study on user-experience

Abstract: Introduction: Transdermal alcohol monitors, such as Secure Continuous Remote Alcohol Monitors (SCRAMs), enable continuous measurement of alcohol consumption in participants' natural environments free from recall bias and response burden. This paper explores young research participants' experience of wearing SCRAMs to provide insights into the potential of the devices to be used for research on a larger scale. Method:In south-east Australia, participants were recruited among festival attendees (n=12) and colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Furthermore, some participants complained about the size and physical discomfort of wearing the SCRAM, which has been discussed in previous studies (Alessi et al, 2017;Caluzzi et al, 2019). When the 29 participants who did not complete the study were compared with those who did complete the study, 2 statistically significant differences were found (Table 1).…”
Section: Compliance and Feasibilitymentioning
confidence: 82%
“…Furthermore, some participants complained about the size and physical discomfort of wearing the SCRAM, which has been discussed in previous studies (Alessi et al, 2017;Caluzzi et al, 2019). When the 29 participants who did not complete the study were compared with those who did complete the study, 2 statistically significant differences were found (Table 1).…”
Section: Compliance and Feasibilitymentioning
confidence: 82%
“…1a [13]). SCRAM is a relatively bulky ankle bracelet intended primarily for use with criminal justice-involved populations [18,37,38]. SCRAM devices have demonstrated discriminative validity in detecting drinking episodes [12], albeit with limited ability to detect low level drinking [39][40][41][42], and thus appear well suited to their primary intended purpose as abstinence monitors in forensic settings [12,43].…”
Section: Transdermal Sensor Types and Factors Impacting Transdermal A...mentioning
confidence: 99%
“…Thus, transdermal sensors have the potential to assess drinking continuously, passively and unobtrusively by measuring the concentration of alcohol in sweat and insensible perspiration. In addition to their existing application as abstinence monitors in the criminal justice system [12,13], a range of additional uses have been proposed for transdermal sensors, including as relapse-detecting monitors capable of prompting 'just-in-time' addiction intervention [14,15], as drinking risk-level indicators to inform the advisability of driving [14,16,17] and as continuous trackers capable of unobtrusively assessing drinking during the course of months and even years for implementation in research studies [5,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Given the low number of persons who receive interlock devices, the study provided no evidence on effects of interlock devices on motor vehicle crashes. Evaluations of SCRAM devices have been based on small samples, limiting conclusions that can be made about their effectiveness (see e.g., Marques and McKnight 2009;Caluzzi et al 2019).…”
Section: Incapacitationmentioning
confidence: 99%